The Missing : Sent - Book 2 - Haddix, Margaret Peterson (New York : Simon & Schuster Books for Young Readers, 2009)
Jonah, Katherine, Chip, and Alex suddenly find themselves in 1483 at the Tower of London, where they discover that Chip and Alex are Prince Edward V and Richard of Shrewsbury, imprisoned by their uncle, King Richard III, but trying to repair history without knowing what is supposed to happen proves challenging. Author's note includes historical facts about the princes and king.
Ages 8-12.
A Junior Library Guild selection
Keywords: Edward -- V, -- King of England, -- 1470-1483 -- Fiction; Richard, -- Duke of York, -- 1472-1483 -- Fiction; Richard -- III, -- King of England, -- 1452-1485 -- Fiction; Edward -- V, -- King of England, -- 1470-1483 -- Fiction; Richard, -- Duke of York, -- 1472-1483 -- Fiction; Richard, -- III, -- King of England, -- 1452-1485 -- Fiction; Space and time -- Fiction; Space and time -- Fiction; Fiction; Great Britain -- Fiction -- History -- Richard III, 1483-1485; Great Britain -- Fiction -- History -- Richard III, 1483-1485